Pelatihan Implementasi Sistem Monitoring Laporan Keuangan Study Kasus Dinas Koperasi Kabupaten Jember - Taufiq Timur Warisaji; Ulya Anisatur Rosyidah (Indonesian Journal Publisher, 2022)
Development of the Village Creative Economy Industry Based on Local Wisdom and Entrepreneurship is one of the flagship programs to be achieved from this service. The creative economy is an evolution of concepts based on creative assets that can generate economic growth and development. Minister of Cooperatives and UKM, Teten Masduki revealed that the creative economy community (Ekraf) is most likely in the national economy. In order to increase their productivity, the Ministry of Cooperatives and UKM, encourages the creative economy community to consolidate into a format. The Department of Cooperatives and Micro Enterprises of Jember Regency in running one of the services encountered several obstacles, namely there were still many cooperatives that had not reported financial reports and RATs in accordance with standards. Financial Information System training and development is one of the efforts made to resolve these obstacles. This Financial Information System will be used by the Department of Cooperatives to carry out Monitoring and Evaluation of the implementation of the Financial Reports and RATs of each of the cooperatives under its guidance. The end result of this service is in the form of a Financial System Training Module that can be used to facilitate cooperatives in carrying out financial reporting in accordance with established standards.